Genetic effects on preweaning weight gain of Nelore-Hereford calves according to different models and estimation methods - Carvalheiro, R. [UNESP]; Pimentel, E. C G [UNESP]; Cardoso, V.; Queiroz, S. A. [UNESP]; Friest, L. A. (Oxford University Press (OUP), 2006)
Additive and nonadditive genetic effects on preweaning weight gain (PWG) of a commercial crossbred population were estimated using different genetic models and estimation methods. The data set consisted of 103,445 records on purebred and crossbred Nelore-Hereford calves raised under pasture conditions on farms located in south, southeast, and middle west Brazilian regions. In addition to breed additive and dominance effects, the models including different epistasis covariables were tested. Models considering joint additive and environment (latitude) by genetic effects interactions were also applied. In a first step, analyses were carried out under animal models. In a second step, preadjusted records were analyzed using ordinary least squares (OLS) and ridge regression (RR). The results reinforced evidence that breed additive and dominance effects are not sufficient to explain the observed variability in preweaning traits of Bos taurus x Bos indicus calves, and that genotype x environment interaction plays an important role in the evaluation of crossbred calves. Data were ill-conditioned to estimate the effects of genotype x environment interactions. Models including these effects presented multicolinearity problems. In this case, RR seemed to be a powerful tool for obtaining more plausible and stable estimates. Estimated prediction error variances and variance inflation factors were drastically reduced, and many effects that were not significant under ordinary least squares became significant under RR. Predictions of PWG based on RR estimates were more acceptable from a biological perspective. In temperate and subtropical regions, calves with intermediate genetic compositions (close to 1/2 Nelore) exhibited greater predicted PWG. In the tropics, predicted PWG increased linearly as genotype got closer to Nelore. ©2006 American Society of Animal Science. All rights reserved.
Keywords: Crossbreeding; Epistasis; Genotype x environment interaction; Heterosis; Multicolinearity; Ridge regression; animal; biological model; Brazil; cattle; cross breeding; environment; genetics; genotype; growth, development and aging; weaning; weight gain; Animals; Cattle; Crosses, Genetic; Environment; Genotype; Models, Biological; Weaning; Weight Gain; Animalia; Bos taurus x Bos indicus